Acupuncture for Low-Back Pain - Sudhakaran, Poovadan (Med Acupunct, 2021)
Low-back pain affects 84% of the world's population. At present, no method of treatment can be considered as the method of choice. Acupuncture is effective, scientific, cost-effective, and free from major side-effects. Three illustrative cases, showing the beneficial effects of acupuncture are presented. Attention is drawn to the possible presence of underlying sacroiliac-joint dysfunction, which could masquerade as sciatica, hip pain, and/or groin pain.